Evaluation of quality parameters for fresh, used and recycled palm olein - Khor, Yih Phing; Sim, Biow Ing; Abas, Faridah; Lai, Oi Ming; Wang, Yong; Nehdi, Imededdine Arbi; Sbihi, Hassen Mohamed; Gewik, Mohamed Mossad; Tan, Chin Ping (John Wiley & Sons, 2019)
Background: Recycled oil has emerged as a significant food safety issue and poses a major threat to public health. To date, very limited studies have been conducted aiming to detect the adulteration of used and recycled palm olein in refined, bleached and deodorized palm olein (RBDPO). In the present study, oil samples that underwent controlled heating and deep-frying studies were refined using the common oil refining procedure to simulate the production of recycled oil. Polymerized triacylglycerol (PTG), oxidized monomeric triacylglycerols (oxTAGs), such as epoxy, keto and hydroxy acids, and caprylic acid have been proposed as potential indicators for tracking the adulteration of recycled oil.